Preheating in end milling of AISI D2 hardened steel with coated carbide inserts - Lajis , M.A.; Amin, A. K. M. Nurul; Karim, A.N. Mustafizul; Hafiz, A. M. K. (Trans Tech Publications, Switzerland, 2010)
This study was conducted to investigate the effect of preheating through inductive heating mechanism in end milling of AISI D2 hardened steel (60-62 HRC) by using coated carbide tool inserts. Apart from preheating, two other machining parameters such as cutting speed and feed were varied while the depth of cut constant was kept constant. Tool wear phenomenon and machined surface finish were found to be significantly affected by preheating temperature and other two variables. End milling operation was performed on a Vertical Machining Centre (VMC). Preheating of the work material to a higher temperature range resulted in a noticeable reduction in tool wear rate leading to a longer tool life. In addition, improved surface finish was obtained with surface roughness values lower than 0.4 um, leaving a possibility of skipping the grinding and polishing operations for certain applications.